Effect of industry specialization of the Iraqi audit firms on audit quality - الطائي, بشرى فاضل; سلمان, حسين فخري (Journal of Economics and Administrative Sciences, 2019)
The research aim to measure the impact of the Industry specialization of the auditors on the quality in audit in Iraqi auditing firms, as well as measuring the factors of Industry specialization in the Iraqi audit companies by measuring the market shares of Iraqi audit firms that audit the companies listed on the Iraqi Stock Exchange For 2010 to 2016, by surveying the opinions of (35) Audit firm on the impact of the Industry specialization of auditing firms in audit quality factors, The effect of the variables was revealed through the use of the survey form Distributed to Iraqi audit companies, The industry specialization of auditing companies was measured by calculating the market share using the information contained in the financial statements published by the Iraqi Stock Exchange for the period from 2010 to 2016 and using the correlation coefficient to analyze the results of the survey. After testing the hypothesis of the research, a set of conclusions was reached, were represented as the auditors in the Iraqi audit firms his Industry specialization, As well as the impact of the Industry specialization of the auditor on audit quality on the Iraqi audit firms, The Industry specialization leads to an increase in the audit quality process through the discovery of the fundamental errors resulting from fraud or errors, which leads to maintaining the confidence of the financial community in the audit profession, The researchers recommend the need for legislative and regulatory bodies in Iraq to emphasize the importance of Industry specialization and the need to exercise auditors for Industry specialization during the implementation of the audit process, which leads to increased quality audit.